Plasmodium yoelii Erythrocyte Binding Like Protein Interacts With Basigin, an Erythrocyte Surface Protein - Yuguchi, Takaaki; Kanoi, Bernard N.; Nagaoka, Hikaru; Miura, Toyokazu; Ito, Daisuke; Takeda, Hiroyuki; Tsuboi, Takafumi; Takashima, Eizo; Otsuki, Hitoshi (Frontiers in Cellular and Infection Microbiology, 2021)
Erythrocyte recognition and invasion is critical for the intra-erythrocytic development of Plasmodium spp. parasites. The multistep invasion process involves specific interactions between parasite ligands and erythrocyte receptors. Erythrocyte-binding-like (EBL) proteins, type I integral transmembrane proteins released from the merozoite micronemes, are known to play an important role in the initiation and formation of tight junctions between the apical end of the merozoite and the erythrocyte surface. In Plasmodium yoelii EBL (PyEBL), a single amino acid substitution in the putative Duffy binding domain dramatically changes parasite growth rate and virulence. This suggests that PyEBL is important for modulating the virulence of P. yoelii parasites. Based on these observations, we sought to elucidate the receptor of PyEBL that mediates its role as an invasion ligand. Using the eukaryotic wheat germ cell-free system, we systematically developed and screened a library of mouse erythrocyte proteins against native PyEBL using AlphaScreen technology. We report that PyEBL specifically interacts with basigin, an erythrocyte surface protein. We further confirmed that the N-terminal cysteine-rich Duffy binding-like region (EBL region 2), is responsible for the interaction, and that the binding is not affected by the C351Y mutation, which was previously shown to modulate virulence of P. yoelii. The identification of basigin as the putative PyEBL receptor offers new insights into the role of this molecule and provides an important base for in-depth studies towards developing novel interventions against malaria.